2015
DOI: 10.11648/j.ajche.s.2015030201.11
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Starch on the Mechanical and Rheological Properties of Polypropylene

Abstract: Abstract:Blends of starch (tapioca) and polypropylene were prepared in various wt/wt concentrations ranging from 100% polypropylene resins to 5:95, 10:90, 20:80, 30:70, 40:60, and 50:50 wt% starch to wt% polypropylene blends. Then the rheological and mechanical properties of the resulting blends were determined using Plastometer and Universal Testing Machine respectively. Tensile strength, percentage elongation, flexural modulus, Izod impact, vicat softening temperature and melt flow index tests were carried o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
1
2
0
1
Order By: Relevance
“…The data also show a trend of increasing film flexibility as PCL to starch ratio was reduced, unlike with a previous study [3]. Tensile strength is inversely proportional to starch content, similar to past research [12,13]. The amorphous structure created by gelatinized starch may explain these findings.…”
Section: Chemical Composition (Starch)supporting
confidence: 72%
“…The data also show a trend of increasing film flexibility as PCL to starch ratio was reduced, unlike with a previous study [3]. Tensile strength is inversely proportional to starch content, similar to past research [12,13]. The amorphous structure created by gelatinized starch may explain these findings.…”
Section: Chemical Composition (Starch)supporting
confidence: 72%
“…Aspect ratio is the most effective on the strength and stiffness of WPCs made of WF and PP (Stark and Rowlands 2003). Pure starch has high bending strength and is flexible; hence, by entering a PP matrix material, increases the bending properties thereof and behaves as a stiffening agent (Oduola and Akpeji 2015). Mousavi et al (2015) obtained different results and found that by increasing the weight percentage of starch in produced composites, the bending properties decreased, while contrary to their finding.…”
Section: Fig 2 Tensile Strength and Tensile Modulus Results Of Tested Compositesmentioning
confidence: 98%
“…By the entrance and increase in SP in the composition, the composite tensile strength was reduced, because the pure starch tensile strength is 90% lower than that of pure PP (Oduola and Akpeji 2015), therefore, a decrease in PP weight percentage in composite structure and replacing it with starch, the final tensile strength of the composites containing starch would reduce. The tensile modulus is increased because pure starch is very flexible (Oduola and Akpeji 2015) and may increase the flexibility by entering the composite, consequently increasing the tensile modulus. Mousavi et al (2015) obtained different results that might be due to differences in the composition of the composites and the different volumes of materials used.…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…A concentração do amido na blenda também é um fator de grande importância, pois quando adicionados em altas concentrações há perda das propriedades (MARTINS, 2015). Oduola (2015) estudou o efeito da adição de diferentes concentrações de amido (de 5% a 50%) em blendas com PP. Observou-se que, em relação ao amido, quanto maior sua concentração nas blendas, menor é o índice de fluidez, devido ao aumento da viscosidade, e menor é o valor da resistência de tração, devido a redução dos valores de tensão no escoamento e na ruptura.…”
Section: Introductionunclassified